Wireless communication with miniaturized sensor devices in swimming - Lecoutere, J.; Puers, R. (Procedia Engineering, 2014)
Assessing the performance of athletes is an on-going research topic. In this paper, research has been conducted towards the monitoring of swimming motion using accelerometers and gyroscopes and towards the transmission of this data in real-time to the poolside in a wireless sensor network. Wearable systems provide several advantages compared to the more commonly used video capturing methods. However, challenges remain in the miniaturisation, wearability and robustness of these systems. Also the wireless communication in the aquatic environment presents significant challenges. Higher carrier frequencies lead to a higher attenuation effect due to the water and lower frequencies lead to a lower comfort due to increasing antenna size, hence presenting a trade-off. This paper presents a new miniaturized sensor system that is able to measure the tri-axial angular velocity and acceleration of a swimmer with an on-board transceiver at 433MHz and an on-board memory for data logging.